Dual role of a (p)ppGpp‐ and (p)ppApp‐degrading enzyme in biofilm formation and interbacterial antagonism. Issue 6 (25th January 2021) - Steinchen, Wieland; Ahmad, Shehryar; Valentini, Martina; Eilers, Kira; Majkini, Mohamad; Altegoer, Florian; Lechner, Marcus; Filloux, Alain; Whitney, John C.; Bange, Gert
Abstract: The guanosine nucleotide‐based second messengers ppGpp and pppGpp (collectively: (p)ppGpp) enable adaptation of microorganisms to environmental changes and stress conditions. In contrast, the closely related adenosine nucleotides (p)ppApp are involved in type VI secretion system (T6SS)‐mediated killing during bacterial competition. Long R elA‐S poT H omolog (RSH) enzymes regulate synthesis and degradation of (p)ppGpp (and potentially also (p)ppApp) through their synthetase and hydrolase domains, respectively. S mall a larmone h ydrolases (SAH) that consist of only a hydrolase domain are found in a variety of bacterial species, including the opportunistic human pathogen Pseudomonas aeruginosa . Here, we present the structure and mechanism of P. aeruginosa SAH showing that the enzyme promiscuously hydrolyses (p)ppGpp and (p)ppApp in a strictly manganese‐dependent manner. While being dispensable for P. aeruginosa growth or swimming, swarming, and twitching motilities, its enzymatic activity is required for biofilm formation. Moreover, (p)ppApp‐degradation by SAH provides protection against the T6SS (p)ppApp synthetase effector Tas1, suggesting that SAH enzymes can also serve as defense proteins during interbacterial competition. Abstract : The genome of Pseudomonas aeruginosa encodes, besides the long RSH enzymes RelA and SpoT, the small alarmone hydrolase SAH that hydrolyses (p)ppGpp and the related (p)ppApp molecules in vitro in a manganese‐dependent manner. SAH is required for biofilm formation of P. aeruginosa and attenuates the toxicity of the type VI secretion system effector protein and (p)ppApp synthetase Tas1 during interbacterial competition. This study thus highlights the functional relevance of SAH enzymes for bacteria.